Assessing Texas School Social Work Practice: Findings from the First Statewide Conference Survey - Xiao Ding; Monica Faulkner; Cynthia Franklin; Beth Gerlach; Mary Beer; Eboni Calbow; Swetha Nulu (International Journal of School Social Work, 2022)
Abstract Aims: To examine the characteristics, perceived barriers, special student populations, and school-based tasks performed by Texas's school social workers in comparison to other Specialized Instructional Services Providers (SISP) professionals in schools. Methods: A convenience sample from a survey of 212 school social workers and school services providers from the Texas School Social Workers Conference. The survey was developed using previous surveys and practice knowledge and assessed (a) demographics, (b) characteristics of school social work practice, (c) types of tasks, (d) special population served, (e) types of barriers), and (f) the tools and training that are most needed. Results: The roles of Texas School social workers are similar to school social workers nationally. There were significant differences between the roles, tasks, and barriers to practice for school social workers than other SISP providers. School social workers more frequently served on the frontlines with high-needs students and special populations, assisted teachers in classroom management and contributed to in-service training for the school than other SISP professionals. Practice Implications: School social workers make significant and sustained contributions to K-12, public schools, magnet schools, and charter schools. School social workers play a key role in serving a school’s high-needs students and specialized populations; better implementation of state standards, professional development, and opportunities for networking are needed.
Keywords: Keywords: School social work; Texas survey; at-risk students; school mental health; research on roles